2010
DOI: 10.1021/je1000473
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor−Liquid Equilibria for Binary and Ternary Mixtures of Methanol, Ethanoic Acid, and Propanoic Acid

Abstract: Vapor-liquid equilibrium (VLE) data for the strongly associating ternary system methanol + ethanoic acid + propanoic acid and three constituent binary systems: methanol + ethanoic acid, methanol + propanoic acid, and ethanoic acid + propanoic acid have been determined by different liquid-phase compositions using a novel pump ebulliometer at 101.3 kPa. The vapor-phase compositions y of these binary systems had been calculated from T-p-x according to the Q function of molar excess Gibbs energy by the indirect me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In Table , the densities and refractive indices at 293.15 K together with the normal boiling points of the pure components are compared with those from the reference of Riddick et al The results confirm that the measurement values closely approach those of the literature. The methods for measuring densities and refractive indices of the compositions have been previously reported. ,, The densities were determined at 293.15 K with a bicapillary pycnometer formerly explained by Rao and Naidu, with a precision of ±0.01 kg·m –3 , and the refractive indexes of the pure components were determined with an Abbe refractometer (Carl-Zeiss-Jena, accuracy ±0.0001) at 293.15 K after calibration with standard samples, equipped with the device.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table , the densities and refractive indices at 293.15 K together with the normal boiling points of the pure components are compared with those from the reference of Riddick et al The results confirm that the measurement values closely approach those of the literature. The methods for measuring densities and refractive indices of the compositions have been previously reported. ,, The densities were determined at 293.15 K with a bicapillary pycnometer formerly explained by Rao and Naidu, with a precision of ±0.01 kg·m –3 , and the refractive indexes of the pure components were determined with an Abbe refractometer (Carl-Zeiss-Jena, accuracy ±0.0001) at 293.15 K after calibration with standard samples, equipped with the device.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for measuring densities and refractive indices of the compositions have been previously reported. 13,14,28 The densities were determined at 293.15 K with a bicapillary pycnometer formerly explained by Rao and Naidu, 29 with a precision of ±0.01 kg•m −3 , and the refractive indexes of the pure components were determined with an Abbe refractometer (Carl-Zeiss-Jena, accuracy ±0.0001) at 293.15 K after calibration with standard samples, equipped with the device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Guan et al investigated that the isobaric vapor-liquid equilibria for water + ethanoic acid + n-pentyl acetate, isopropyl acetate, N-methyl pyrrolidone, or N-methyl acetamide were correlated and predicted by both the nonrandom two-liquid (NRTL) and universal quasichemical activity coefficient (UNIQUAC) models used in combination with the Hayden-O'Connell (HOC) method [11][12][13][14]. In our recent work, we have concluded that the VLE data for the associating systems containing the carboxylic acid system can be correlated and predicted [15,16]. Although the VLE data of the mixture containing the associating systems were previously reported by the different research groups [17][18][19][20][21], respectively, the VLE data for the associating binary system containing the carboxylic acid have been still extensively studied because of the extensive association effects occurring in them and the difficulty of properly calculating the activity coefficients [22][23][24][25].…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the challenge for the VLE data of the associating systems has evoked more and more researchers to focus on new strategies for exploring them. The VLE data for methanol + water + ethanoic acid ternary system and the constituent binary systems are indispensable in distillation separation process to the product of methanol carboxylation through the correlation and prediction by the new method, while some of the isobaric VLE data for these binary and ternary systems are correlated and predicted earlier [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. To provide the new correlation and prediction for some necessary basic thermodynamic data on the separation process of methanol carboxylation, therefore, it is very indispensable for these systems studied on the VLE data of the constituent binary and ternary systems using the new method.…”
Section: Introductionmentioning
confidence: 99%